Diverse morphologies of soft palate in normal individuals: A cephalometric perspective - Kruthika S Guttal; Rohit Breh; Ramaprakasha Bhat; Krishna N Burde; Venkatesh G Naikmasur (Wolters Kluwer Medknow Publications, 2012)
Purpose: Soft palate plays a significant role in various important functions in the head and neck region- Its varied morphology is implicated in variety of diseases. Therefore, it is essential to establish the morphology of soft palate in normal patients to establish the variations in its morphology in various diseases. The present study aims to investigate the variation of the soft palate morphology in Indian subpopulation and possibly classify types of soft palate, to evaluate the dimensional differences of the soft palate between each types and to investigate the proportional differences in different age and gender groups. Materials and methods: Two hundred digital lateral cephalograms were analyzed for the velar morphology and categorized into different types. In addition length and thickness of the soft palate was also measured. Results: In addition to original seven types of soft palate two more morphological variants of soft palate were observed. The velar length was significantly higher in males and the velar width was significantly less in females. Also a significant increase in velar length was observed with increase in age. Conclusion: Type 1 was the most common of all the variants. Moreover, additional morphological variants which did not fit into the classical categories were also observed. There was no significant correlation between the different age groups and the types of soft palate. The velar length and width was significantly greater in males than in females. A significant increase in velar length was noted with increase in age.